Da penhora de faturamento - Hernandez, José Rubens (2003)
The study objective of this dissertation consists of the income attachment which field of study is in Civil Procedural Law. The first part begins with the examination of the lack of effectiveness in the execution that led to the income attachment as an effort to solve this problem. Next, there is a study of the attachment principie to configure its main characteristics, broaching a brief description of the attachment itself. The fact that it falls on individuais and legal entities observing what is the best classification, constriction of money and rights besides the study of the income for the best delimitation of the objective of the study and also the limits to be observed in this type of constriction. lhe first part of the study is also about the legal requirement and its admissibility, the trustee as well as the burden of the creditor and whom the execution is beneficiai to. The second part of the study approaches the impugnation of the income attachment and the vices that may affect it, the means used to contest the decisions that solve matters related to this figure, studying the bill of review, writ of mandamus, interplea and habeas corpus. The conclusion joins the positions that could be taken in the course of this study and it would not be possible without criticizing the income attachment as it is . today - easy to be understood but it brings innumerable problems that can make the execution impracticable.